2021
DOI: 10.1017/s0144686x2100101x
|View full text |Cite
|
Sign up to set email alerts
|

‘100 metres to the liquor store and 300 meters to the cemetery’ – individual, social, environmental and organisational facilitators and barriers to thriving in Swedish sheltered housing models

Abstract: In Sweden, sheltered housing is a housing model that provides accessible apartments with elevated social possibilities for older people. The environment within sheltered housing is expected to support resident health and reduce the need for care services. A previous study has shown that with increasing levels of depressive mood and decreasing levels of self-rated health and functional status, those residing in sheltered housing report higher levels of thriving compared to those ageing in place. Therefore, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…However, a previous study on the same sample has shown that, despite no differences in self-reported wellbeing, those residing in sheltered housing generally reported higher levels of thriving compared to those aging in place, when experiencing decreasing levels of self-rated health and functional status and increasing level of depressive mood (Corneliusson et al, 2019a). Furthermore, a qualitative study on thriving in Swedish sheltered housing found four levels of facilitators and barriers to thriving in Swedish sheltered housing; individual factors, social context, environmental factors and organizational context (Corneliusson et al, 2021). These results of previous studies imply that there are features within sheltered housing that support thriving and are appreciated by residents: however, further studies are needed to determine if, how and to what extent the features that facilitate thriving can potentially support residents despite decreasing health or increased loneliness and/or vice versa; that perceived accessibility of support is a strong predictor of thriving.…”
Section: Discussionmentioning
confidence: 99%
“…However, a previous study on the same sample has shown that, despite no differences in self-reported wellbeing, those residing in sheltered housing generally reported higher levels of thriving compared to those aging in place, when experiencing decreasing levels of self-rated health and functional status and increasing level of depressive mood (Corneliusson et al, 2019a). Furthermore, a qualitative study on thriving in Swedish sheltered housing found four levels of facilitators and barriers to thriving in Swedish sheltered housing; individual factors, social context, environmental factors and organizational context (Corneliusson et al, 2021). These results of previous studies imply that there are features within sheltered housing that support thriving and are appreciated by residents: however, further studies are needed to determine if, how and to what extent the features that facilitate thriving can potentially support residents despite decreasing health or increased loneliness and/or vice versa; that perceived accessibility of support is a strong predictor of thriving.…”
Section: Discussionmentioning
confidence: 99%